Ireland's Too Big to Fail vs. Iceland's Too Big to Bail: Comparison of Policy responses and Post Crisis Recovery - Eva V. Markúsdóttir 1988- (2011)
This thesis aims to compare Ireland's and Iceland's policy responses to the economic crisis as well as their post-crisis recovery. Both originated with an overextended banking sector, however, the countries responded unlike to failure of their banks. Ireland bailed out its bank with financial guarantee being extended at the cost of its taxpayers whereas Iceland did not qualify for such a bailout. A specific focus is on the fact that Ireland is a member of the European Monetary Union and that Iceland has its own monetary policy.